Etika Bisnis Online Busana Muslim Ditinjau dari Perspektif Islam di Kota Mataram (Studi Kasus dikalangan Mahasiswa Peguruan Tinggi Negeri) - Mariana Mariana; Busaini Busaini; Akhmad Jupri (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
This study aims to determine the application of the Muslim Clothing Online Business Ethics in the City of Mataram and the suitability of the Online business with the Islamic Perspective. This research uses descriptive qualitative research methods. The collection technique uses observation, interview, and documentation techniques. While the data analysis technique uses data reduction techniques, data presentation, and conclusions / verification. The results of the study are: (1) The informant in this study stated that the Muslim fashion online business transaction in Mataram City has not yet fully run an online Muslim fashion business. Based on the principles of business ethics of buying and selling in Islamic economics namely siddiq, tablik, amanah and fathonah, onlineshop sellers have not carried out these principles. Siddiq principle (honesty), online sellers only explain the condition of Muslim clothing that is sold with a description of the image in the online shop application, without explaining in detail and honest both the condition of the material, size, color and defects. (2) The application of online business ethics in Muslim fashion in the city of Mataram is not in accordance with the principles of business ethics in the view of Islamic law because online sellers are not completely honest in explaining the condition of goods sold, when shipping goods online sellers are often not suitable for delivering goods ordered by consumers both from in terms of quality and quantity.